Thermoplastic polyester resin composition and molded article thereof

The resin composition, combining crystalline polyester resin with specific amorphous and hydroxyl-containing resins, addresses the challenge of balancing heat resistance, low sled properties, and mechanical properties, achieving superior performance in demanding applications.

JP2025059016APending Publication Date: 2025-04-09TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024164716
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-09-24
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing thermoplastic polyester resin compositions struggle to achieve a balance between excellent heat resistance, low sled properties, and mechanical properties, particularly in applications requiring high impact resistance and dimensional stability.

Method used

A resin composition comprising 100 parts by mass of crystalline polyester resin, 1 to 110 parts by mass of amorphous resin, and 0.1 to 40 parts by mass of at least one resin selected from hydrogenated petroleum resin, terpene resin, hydrogenated terpene phenol resin, and hydroxyl group-containing acrylic resin, optionally blended with an inorganic filler.

Benefits of technology

The composition achieves excellent heat resistance, low sled properties, and enhanced mechanical properties, making it suitable for various applications including electrical and electronic equipment parts, and automobile components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059016000001
    Figure 2025059016000001
  • Figure 2025059016000002
    Figure 2025059016000002
Patent Text Reader

Abstract

To provide a thermoplastic polyester resin composition excellent in heat resistance, low warpage properties and mechanical characteristics, and a molded article thereof.SOLUTION: The resin composition contains the following components [A], [B] and [C]: [A] a crystalline polyester resin; [B] an amorphous resin; and [C] at least one resin selected from a hydrogenated petroleum resin, a terpene resin, a hydrogenated terpene phenol resin and a hydroxyl group-containing acrylic resin. The resin composition contains 1-110 pts.mass of the component [B] and 0.1-40 pts.mass of the component [C] based on 100 pts.mass of the component [A].SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a thermoplastic polyester resin composition having excellent heat resistance, low warpage (reduced warpage) and mechanical properties, and to a molded article thereof. [Background technology]

[0002] Polyester resins, especially polybutylene terephthalate resins, have excellent mechanical properties, insulation, heat resistance, and moldability, and are therefore widely used in a variety of containers, films, electrical and electronic equipment parts, automotive parts, machine parts, and more.

[0003] In particular, electrical components for automobiles require high dimensional precision and heat resistance to withstand use in high-temperature environments.

[0004] Polybutylene terephthalate resin is a crystalline resin, so it has a large molding shrinkage rate, and when fibrous reinforcing materials are blended, it tends to have a large anisotropy, making it prone to warping in molded products. To reduce warping, methods have been proposed in which various amorphous resins are blended, but this has the problem of reducing heat resistance and mechanical properties depending on the amount of amorphous resin blended.

[0005] Furthermore, in order to improve the mechanical properties of molded articles obtained from polyester resins, one method is to add an inorganic filler such as a fibrous reinforcing material to the thermoplastic polyester resin. However, if the amount of fibrous reinforcing material added is increased, not only will the above-mentioned warping occur due to the anisotropy of the reinforcing material, but problems will also arise, such as deterioration in the appearance of the product, such as roughness on the surface of the molded article and loss of gloss due to a decrease in the fluidity of the polyester resin composition.

[0006] Patent Document 1 discloses a resin composition obtained by blending 0.1 to 150 parts by weight of (F) a reinforcing filler with 100 parts by weight of a resin composition blended with 95 to 10% by weight of (A) a thermoplastic polyester resin, 4 to 50% by weight of (B) a rubber-modified styrene-based thermoplastic resin, 1 to 40% by weight of (C) a polyphenylene ether resin, 0.01 to 4% by weight of (D) a phosphite ester compound, and 0.1 to 20% by weight of (E) a phosphate ester compound, as a method for improving the low warpage and mechanical properties (impact resistance) of a polyester resin composition.

[0007] Furthermore, Patent Document 2 discloses a thermoplastic resin composition containing (A) 15 to 50 parts by mass of a polybutylene terephthalate resin having an intrinsic viscosity of 0.3 to 0.75 dL / g, (B) 50 to 85 parts by mass of an acrylonitrile-styrene copolymer having a weight-average molecular weight of 200,000 or more, and (C) 5 to 100 parts by mass of glass fibers, relative to a total of 100 parts by mass of (A) and (B), as a method for achieving both high heat resistance and low warpage. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Laid-Open No. 2002-179890 [Patent Document 2] Japanese Patent Publication No. 2020-186293 Summary of the Invention [Problem to be solved by the invention]

[0009] However, although the invention disclosed in Patent Document 1 has excellent impact resistance, further improvement is required in terms of low warpage.

[0010] Furthermore, in recent years, as parts have become smaller and thinner, higher levels of mechanical properties, particularly impact resistance, are required to prevent cracks and chips during part assembly. The invention disclosed in Patent Document 2 has excellent low warpage properties but poor impact resistance, and does not achieve high levels of heat resistance, low warpage, and mechanical properties.

[0011] Therefore, an object of the present invention is to provide a thermoplastic polyester resin composition having excellent heat resistance, low warpage and mechanical properties, and a molded article thereof. [Means for solving the problem]

[0012] In order to solve the above problems, the present invention provides the following means. 1. A resin composition containing components [A], [B], and [C], wherein the resin composition contains 1 to 110 parts by mass of component [B] and 0.1 to 40 parts by mass of component [C] when the component [A] is taken as 100 parts by mass. [A] Crystalline polyester resin [B] Amorphous resin [C] At least one resin selected from hydrogenated petroleum resins, terpene resins, hydrogenated terpene phenolic resins, and hydroxyl group-containing acrylic resins 2. The resin composition according to item 1, wherein the component [C] is a resin having a hydroxyl value of 10 mg-KOH / g or more. 3. The resin composition according to item 1 or 2, further comprising an inorganic filler as component [D]. 4. The resin composition according to item 3, comprising 70 to 110 parts by mass of the component [B], 0.1 to 40 parts by mass of the component [C], and 0.1 to 200 parts by mass of the component [D] relative to 100 parts by mass of the component [A]. 5. The resin composition according to any one of items 1 to 4, wherein the component [A] is polybutylene terephthalate. 6. The resin composition according to any one of items 1 to 5, wherein the component [B] is a polymer containing a styrene skeleton. 7. The resin composition according to any one of items 1 to 6, wherein the component [B] is a polymer containing an acrylonitrile skeleton and a styrene skeleton. 8. A molded article made of the resin composition according to any one of items 1 to 7. [Effects of the Invention]

[0013] According to the present invention, it is possible to provide a thermoplastic polyester resin composition having excellent heat resistance, low warpage (reduced warpage) and mechanical properties, and a molded article thereof.

[0014] Therefore, molded articles made from the thermoplastic resin composition of the present invention can be suitably used for parts of various electric and electronic devices, interior or exterior parts of automobiles, and the like. DETAILED DESCRIPTION OF THE INVENTION

[0015] The resin composition of the present invention contains 100 parts by mass of a crystalline polyester resin as component [A], 1 to 110 parts by mass of an amorphous resin as component [B], and 0.1 to 40 parts by mass of at least one resin selected from a hydrogenated petroleum resin, a terpene resin, and a hydrogenated terpene phenol resin as component [C] (hereinafter, sometimes abbreviated as "component [C]").

[0016] Each component of the resin composition of the present invention will be described in detail below.

[0017] [[A] Crystalline polyester resin] The crystalline polyester resin [A] used in the present invention has crystallinity. "Crystalline" here means that at least one crystalline melting endothermic peak of 1 J / g or more is observed in the range of 50 to 300°C in differential scanning calorimetry at a heating rate of 10°C / min. The temperature at which the crystalline melting endothermic peak is observed is preferably in the range of 150 to 300°C, more preferably 200 to 300°C, from the viewpoint of improving heat resistance.

[0018] The crystalline polyester resin [A] used in the present invention is a polymer or copolymer having, as its main structural unit, at least one residue selected from the group consisting of (1) dicarboxylic acid or its ester-forming derivative and diol or its ester-forming derivative, (2) hydroxycarboxylic acid or its ester-forming derivative, and (3) lactone. Here, "having as the main structural unit" refers to having at least one residue selected from the group consisting of (1) to (3) in 50 mol % or more of all structural units, with a preferred embodiment being having at least 80 mol % of such residues. Among these, polymers or copolymers having, as their main structural units, (1) residues of dicarboxylic acid or its ester-forming derivative and diol or its ester-forming derivative are preferred due to their superior mechanical properties and heat resistance.

[0019] Examples of the dicarboxylic acid or its ester-forming derivative include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, bis(p-carboxyphenyl)methane, 1,4-anthracenedicarboxylic acid, 1,5-anthracenedicarboxylic acid, 1,8-anthracenedicarboxylic acid, 2,6-anthracenedicarboxylic acid, 9,10-anthracenedicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-tetrabutylphosphoniumisophthalic acid, and 5-sodiumsulfoisophthalic acid; aliphatic dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, malonic acid, glutaric acid, and dimer acid; alicyclic dicarboxylic acids such as 1,3-cyclohexanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; and ester-forming derivatives thereof. Two or more of these may be used.

[0020] Examples of the diol or its ester-forming derivative include aliphatic or alicyclic glycols having 2 to 20 carbon atoms, such as ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, decamethylene glycol, cyclohexanedimethanol, cyclohexanediol, and dimer diol; long-chain glycols having a molecular weight of 200 to 100,000, such as polyethylene glycol, poly-1,3-propylene glycol, and polytetramethylene glycol; aromatic dioxy compounds, such as 4,4'-dihydroxybiphenyl, hydroquinone, t-butylhydroquinone, bisphenol A, bisphenol S, and bisphenol F; and ester-forming derivatives thereof. Two or more of these may be used.

[0021] Examples of polymers or copolymers having dicarboxylic acid or its ester-forming derivative and diol or its ester-forming derivative as structural units include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polypropylene isophthalate, polybutylene isophthalate, polybutylene naphthalate, polypropylene isophthalate / terephthalate, polybutylene isophthalate / terephthalate, polypropylene terephthalate / naphthalate, polybutylene terephthalate / naphthalate, polybutylene terephthalate / decanedicarboxylate, polypropylene terephthalate / 5-sodium sulfoisophthalate, polybutylene terephthalate / 5-sodium sulfoisophthalate, polypropylene terephthalate / polyethylene glycol, and polybutylene terephthalate / polyethylene glycol. Examples of suitable aromatic polyester resins include polypropylene glycol, polypropylene terephthalate / polytetramethylene glycol, polybutylene terephthalate / polytetramethylene glycol, polypropylene terephthalate / isophthalate / polytetramethylene glycol, polybutylene terephthalate / isophthalate / polytetramethylene glycol, polybutylene terephthalate / succinate, polypropylene terephthalate / adipate, polybutylene terephthalate / adipate, polypropylene terephthalate / sebacate, polybutylene terephthalate / sebacate, polypropylene terephthalate / isophthalate / adipate, polybutylene terephthalate / isophthalate / succinate, polybutylene terephthalate / isophthalate / adipate, and polybutylene terephthalate / isophthalate / sebacate. These polymers and copolymers may be used alone or in combination of two or more. Here, " / " indicates copolymer.

[0022] Among these, from the viewpoint of further improving mechanical properties and heat resistance, polymers or copolymers having, as main structural units, a residue of an aromatic dicarboxylic acid or an ester-forming derivative thereof and a residue of an aliphatic diol or an ester-forming derivative thereof are more preferred, and polymers or copolymers having, as main structural units, a residue of terephthalic acid, naphthalenedicarboxylic acid or an ester-forming derivative thereof and a residue of an aliphatic diol selected from propylene glycol and 1,4-butanediol or an ester-forming derivative thereof are even more preferred.

[0023] Among these, at least one aromatic polyester resin selected from polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polypropylene naphthalate, polybutylene naphthalate, polypropylene isophthalate / terephthalate, polybutylene isophthalate / terephthalate, polypropylene terephthalate / naphthalate, polybutylene adipate / terephthalate, polybutylene terephthalate / sebacate, and polybutylene terephthalate / naphthalate is particularly preferred, with at least one selected from polyethylene terephthalate, polybutylene terephthalate, polybutylene isophthalate / terephthalate, polybutylene decanedicarboxylate / terephthalate, polybutylene terephthalate / naphthalate, and polybutylene / ethylene terephthalate being more preferred. Two or more of these may also be used in any desired amounts. Polybutylene terephthalate is even more preferred due to its excellent balance of mechanical properties and moldability.

[0024] The acid value of the crystalline polyester resin [A] used in the present invention is preferably 50 eq / t or less from the viewpoints of suppressing deterioration in mechanical properties during melt-kneading and retention of the resin composition obtained by the present invention, and of moldability. It is more preferably 30 eq / t or less, even more preferably 20 eq / t or less, and particularly preferably 10 eq / t or less. The lower limit of the acid value is 0 eq / t. The acid value here is the value measured by dissolving the crystalline polyester resin [A] in an o-cresol / chloroform solvent and then titrating with ethanolic potassium hydroxide.

[0025] The crystalline polyester resin [A] used in the present invention preferably has an intrinsic viscosity of 0.36 dL / g or more, more preferably 0.50 dL / g or more, as measured in an o-chlorophenol solution at 25° C., from the viewpoint of further improving mechanical properties. Furthermore, from the viewpoint of improving fluidity, the intrinsic viscosity is preferably 1.60 dL / g or less, more preferably 1.50 dL / g or less.

[0026] The crystalline polyester resin [A] used in the present invention can be produced by a known polycondensation method, ring-opening polymerization method, etc. The production method may be either batch polymerization or continuous polymerization, and either a transesterification reaction or a direct polymerization reaction may be applied, but from the viewpoint of productivity, continuous polymerization is preferred, and direct polymerization is more preferred.

[0027] When the crystalline polyester resin [A] used in the present invention is a polymer or copolymer obtained by a condensation reaction of a dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative as the main components, it can be produced by subjecting the dicarboxylic acid or its ester-forming derivative and the diol or its ester-forming derivative to an esterification reaction or an ester exchange reaction, followed by a polycondensation reaction.

[0028] In order to effectively promote the esterification reaction or transesterification reaction and polycondensation reaction, it is preferable to add a polymerization catalyst during these reactions. Specific examples of the polymerization catalyst include organotitanium compounds such as methyl ester, tetra-n-propyl ester, tetra-n-butyl ester, tetraisopropyl ester, tetraisobutyl ester, tetra-tert-butyl ester, cyclohexyl ester, phenyl ester, benzyl ester, tolyl ester, or mixed esters thereof of titanic acid, dibutyltin oxide, methylphenyltin oxide, tetraethyltin, hexaethylditin oxide, cyclohexahexylditin oxide, didodecyltin oxide, triethyltin halide, and the like. Examples of suitable tin compounds include tin hydroxide, triphenyltin hydroxide, triisobutyltin acetate, dibutyltin diacetate, diphenyltin dilaurate, monobutyltin trichloride, dibutyltin dichloride, tributyltin chloride, dibutyltin sulfide, butylhydroxytin oxide, alkylstannoic acids such as methylstannoic acid, ethylstannoic acid, and butylstannoic acid, zirconia compounds such as zirconium tetra-n-butoxide, and antimony compounds such as antimony trioxide and antimony acetate. Two or more of these may be used.

[0029] Among these polymerization catalysts, organic titanium compounds and tin compounds are preferred, and tetra-n-butyl ester of titanic acid is more preferred. The amount of the polymerization catalyst added is preferably in the range of 0.01 to 0.2 parts by mass per 100 parts by mass of the crystalline polyester resin [A].

[0030] The polyester resin after polycondensation is removed from the reaction vessel and cooled to a solid state. Generally, the polyester resin is taken out in the form of strands, solidified or semi-solidified in cooling water, and then cut with a strand cutter, or extruded into water and cut with an underwater cutter to form pellets.

[0031] [[B] Amorphous resin] The amorphous resin [B] used in the present invention does not have crystallinity. "Crystalline" here means that at least one crystalline melting endothermic peak of 1 J / g or more is observed in the range of 50 to 300°C in differential scanning calorimetry at a heating rate of 10°C / min. In other words, the amorphous resin [B] is a resin in which no crystalline melting endothermic peak of 1 J / g or more is observed under the above conditions.

[0032] The amorphous resin [B] used in the present invention is not particularly limited as long as it satisfies the above requirements, and various known resins can be used. Specific examples of amorphous resins include (meth)acrylate resins, styrene resins, polycarbonate resins, polyolefin resins, vinyl cyanide resins, polyester resins, polyamide resins, polyarylene sulfide resins, polyacetal resins, polyurethane resins, aromatic or aliphatic polyketone resins, polyarylate resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, poly-4-methylpentene-1, polyetherimide resins, cellulose acetate resins, and polyvinyl alcohol resins. Two or more of these may be used. From the viewpoints of low warpage and improved heat resistance, vinyl cyanide resins and styrene resins are preferred, and acrylonitrile-styrene copolymers, which are polymers containing an acrylonitrile skeleton and a styrene skeleton, are more preferred.

[0033] (Acrylonitrile-styrene copolymer) The content of units derived from acrylonitrile monomers in the acrylonitrile-styrene copolymer is preferably 5 to 50% by weight, more preferably 8 to 35% by weight, and the content of units derived from styrene monomers is preferably 50 to 95% by weight, more preferably 65 to 92% by weight.

[0034] In the present invention, the content of units derived from acrylonitrile monomers and units derived from styrene monomers in the acrylonitrile-styrene copolymer is 1 This is done by H-NMR measurement.

[0035] The melt flow rate (MFR) of the acrylonitrile-styrene copolymer is preferably in the range of 5 to 100 g / 10 min at 220° C. under a load of 10 kg, and more preferably in the range of 5 to 80 g / 10 min.

[0036] The mass average molecular weight (Mw) of the acrylonitrile-styrene copolymer is preferably in the range of 60,000 to 2,200,000, and more preferably 80,000 to 200,000.

[0037] In the present invention, the mass average molecular weight (Mw) of the acrylonitrile-styrene copolymer is measured by GPC (gel permeation chromatography).

[0038] The acrylonitrile-styrene copolymer is preferably an acrylonitrile-styrene copolymer (AS resin) or an acrylonitrile-styrene-glycidyl methacrylate copolymer. The combined use of these two types is particularly preferred from the viewpoint of mechanical properties, as it improves compatibility with the crystalline polyester resin [A].

[0039] There are no particular limitations on the method for producing the acrylonitrile-styrene copolymer, and commonly known methods such as bulk polymerization, solution polymerization, bulk suspension polymerization, suspension polymerization, emulsion polymerization, etc. It is also possible to obtain the above composition by blending resins that have been (graft) copolymerized separately.

[0040] The content of the amorphous resin [B] used in the present invention is 1 part by mass or more and 110 parts by mass or less per 100 parts by mass of the crystalline polyester resin [A]. If the content of the amorphous resin [B] is less than 1 part by mass per 100 parts by mass of the crystalline polyester resin [A], the low warpage property is poor, and if it exceeds 110 parts by mass, the heat resistance is poor. From the viewpoint of low warpage property, the content is preferably 50 parts by mass or more, more preferably 70 parts by mass or more. Furthermore, from the viewpoint of improving heat resistance, the content is preferably 100 parts by mass or less.

[0041] [[C] component] The component [C] used in the present invention is at least one resin selected from the group consisting of hydrogenated petroleum resins, terpene resins, hydrogenated terpene phenol resins, and hydroxyl group-containing acrylic resins.

[0042] The hydrogenated petroleum resin used in the present invention is obtained by hydrogenating a polymer of hydrocarbon compounds that are by-produced during the thermal cracking of naphtha. Examples of such hydrogenated petroleum resins include hydrogenated C9 petroleum resins obtained by polymerizing a C9 fraction consisting of aromatic hydrocarbons, hydrogenated C5 petroleum resins obtained by polymerizing a C5 fraction consisting of aliphatic hydrocarbons, hydrogenated C5-C9 copolymer petroleum resins obtained by copolymerizing a C9 fraction and a C5 fraction as raw materials, and hydrogenated modified petroleum resins obtained by modifying these petroleum resins with maleic anhydride, maleic acid, fumaric acid, (meth)acrylic acid, phenol, etc.

[0043] Examples of C9 petroleum resins include polymers of at least one compound selected from the group consisting of indene, methylindene, vinyltoluene, styrene, α-methylstyrene, and β-methylstyrene as a C9 fraction.

[0044] Examples of C5 petroleum resins include polymers of aliphatic hydrocarbons such as C5 fractions, such as pentene, pentadiene, and isoprene.

[0045] Examples of hydrogenated petroleum resins include Alcon P-125, P-115, P-100, and P-90, and Plafit E610H and E620H, all of which are available from Arakawa Chemical Industries, Ltd.; Imave P-100, P-125, P-140, S-100, and S-110, all of which are available from Idemitsu Kosan Co., Ltd.; and T-REZ HA125, HA105, HA103, HA085, HB125, and HB103, all of which are available from ENEOS Corporation.

[0046] The terpene resin used in the present invention is a resin prepared by polymerizing a terpene monomer. Because terpene monomers have unsaturated bonds in their molecules, they can be polymerized alone or with other monomers to form polymers. Examples of such terpene monomers include α-pinene, β-pinene, carene, α-terpinene, ν-terpinene, d-limonene, dipentene, terpinolene, α-phellandrene, β-phellandrene, paramenthadienes, pyronene, camphene, alloocimene, and myrcene. Preferred examples include d-limonene, dipentene, α-phellandrene, β-phellandrene, and α-terpinene. The terpene resin may be prepared by polymerizing a single terpene monomer or two or more terpene monomers. Furthermore, the terpene resin may be a single terpene monomer or a combination of two or more terpene monomers.

[0047] Examples of terpene resins include the YS Resin PX series and YS Resin PXN series from Yasuhara Chemical Co., Ltd.

[0048] The hydrogenated terpene phenol resin used in the present invention is prepared by copolymerizing the above-mentioned terpene monomer with a phenol, and then subjecting the resin to hydrogenation treatment.

[0049] Examples of hydrogenated terpene phenol resins include the YS Polystar UH series manufactured by Yasuhara Chemical Co., Ltd.

[0050] The hydroxyl group-containing acrylic resin used in the present invention can be obtained as a homopolymer obtained by homopolymerization of a hydroxyl group-containing acrylic monomer, or as a copolymer obtained by a known method such as radical copolymerization of a monomer mixture containing a hydroxyl group-containing acrylic monomer.

[0051] Examples of hydroxyl group-containing acrylic monomers include esters of acrylic acid or methacrylic acid such as 2-hydroxyethyl, 2-hydroxypropyl, 3-hydroxypropyl, or 4-hydroxybutyl, and ring-opening adducts of acrylic acid or 2-hydroxyethyl methacrylate with ε-caprolactone, ethylene oxide, or propylene oxide. These hydroxyl group-containing acrylic monomers may be used alone or in combination of two or more.

[0052] Examples of other monomers copolymerizable with the hydroxyl group-containing acrylic monomer include acrylic acid or methacrylic acid and their methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, hexyl, cyclohexyl, 2-ethylhexyl, lauryl, and stearyl esters, acrylonitrile, methacrylonitrile, acrylamide, methacrylamide, styrene, α-methylstyrene, maleic acid, and vinyl acetate. These copolymerizable monomers may be used alone or in combination with the hydroxyl group-containing acrylic monomer. The polymerization is typically carried out using a known polymerization initiator.

[0053] Hydroxyl-containing acrylic resin has an ester skeleton and is highly compatible with crystalline polyester resin [A], so it deposits little on the surface of molded products and is excellent at preventing mold contamination during molding.

[0054] Examples of hydroxyl group-containing acrylic resins include ARUFON UH-2000 series manufactured by Toagosei Co., Ltd.

[0055] By blending component [C] with crystalline polyester resin [A] and amorphous resin [B], the dispersibility of the crystalline polyester resin [A] and amorphous resin [B] is controlled, making it easier to form a phase structure that exhibits excellent heat resistance.

[0056] From the viewpoint of improving heat resistance, the aromatic skeleton content of the component [C] is preferably 40 mol % or less, more preferably 25 mol % or less, and even more preferably 15 mol % or less. The aromatic skeleton content of the component [C] is measured as a solution in heavy 1,1,2,2-tetrachloroethane, as follows: 1 It is calculated based on the following formula from the unit structure of the [C] component determined by H-NMR. Aromatic skeleton content = (proton integral ratio of peaks attributable to protons of the aromatic skeleton from 6.5 to 8.5 ppm) / {(proton integral ratio of peaks attributable to protons other than those of the aromatic skeleton from 0.5 to 5.8 ppm) + (proton integral ratio of peaks attributable to protons of the aromatic skeleton from 6.5 to 8.5 ppm)} × 100 (mol%) Furthermore, from the viewpoint of improving heat resistance, it is preferable that the component [C] used in the present invention contains hydroxyl groups. The presence of hydroxyl groups controls the dispersibility of the crystalline polyester resin [A] and the amorphous resin [B], making it easier to form a phase structure that exhibits excellent heat resistance. A hydroxyl value of the component [C] of 1 mg-KOH / g or more is considered to contain hydroxyl groups. The hydroxyl value of the component [C] is preferably 5 mg-KOH / g or more, more preferably 10 mg-KOH / g or more, and even more preferably 30 mg-KOH / g or more. There is no particular upper limit for the hydroxyl value, but from the viewpoint of availability, it is preferably 1300 mg-KOH / g or less. The hydroxyl value referred to here is a value measured by neutralization titration of the component [C] (JIS K0070).

[0057] The content of the component [C] used in the present invention is 0.1 to 40 parts by mass per 100 parts by mass of the crystalline polyester resin [A]. If the content of the component [C] per 100 parts by mass of the crystalline polyester resin [A] is less than 0.1 part by mass, the heat resistance, low warpage, and mechanical properties are poor, and if it exceeds 40 parts by mass, the extrusion processability and moldability are poor. From the viewpoint of improving heat resistance, low warpage, and mechanical properties, the content is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more. Furthermore, from the viewpoint of suppressing decomposition during extrusion processing and moldability, 30 parts by mass or less is preferred.

[0058] The component [C] used in the present invention can be a combination of two or more types. The number and parts by weight of the components used in combination are not particularly limited as long as they are within the range of parts by weight described above.

[0059] [[D] Inorganic filler] The resin composition of the present invention preferably further contains an inorganic filler [D]. By further containing the inorganic filler [D], heat resistance and mechanical properties can be improved. The inorganic filler [D] may be a fibrous, plate-like, granular, or amorphous inorganic compound.

[0060] Fibrous inorganic fillers are preferred from the viewpoint of mechanical properties, and specific examples include glass fibers, aramid fibers, carbon fibers, alumina fibers, silicon carbide fibers, cellulose fibers, etc. Glass fibers are more preferred from the viewpoint of mechanical properties.

[0061] The plate-like inorganic filler exhibits the function of reducing anisotropy and warpage, and examples thereof include talc, glass flakes, mica, kaolin, metal foil, etc. Among the plate-like inorganic fillers, glass flakes are preferred.

[0062] Other particulate or amorphous inorganic fillers include ceramic beads, clay, zeolite, barium sulfate, titanium oxide, silicon oxide, aluminum oxide, magnesium hydroxide, zinc sulfide, and the like.

[0063] The glass fibers described above are preferably chopped strand or roving glass fibers. These glass fibers are preferably treated with a silane coupling agent, such as an aminosilane compound or an epoxysilane compound, and / or a sizing agent containing urethane, a copolymer of acrylic acid, such as an acrylic acid / styrene copolymer, a copolymer of maleic anhydride, such as a methyl acrylate / methyl methacrylate / maleic anhydride copolymer, vinyl acetate, bisphenol A diglycidyl ether, or one or more epoxy compounds, such as a novolac epoxy compound. Glass fibers treated with a copolymer of maleic anhydride or a sizing agent containing an epoxy compound are more preferred because they can further improve mechanical properties and hydrolysis resistance during high-temperature molding. The silane coupling agent and / or sizing agent may be mixed in an emulsion liquid before use. The fiber diameter of the glass fibers is typically preferably in the range of 1 to 30 μm. From the viewpoint of dispersibility of the glass fibers in the resin, the lower limit is preferably 5 μm. From the viewpoint of mechanical properties, the upper limit is preferably 15 μm.

[0064] The blending amount of the inorganic filler [D] is preferably 0.1 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the crystalline polyester resin [A]. Blending 1 part by mass or more of the inorganic filler [D] can further improve mechanical properties and heat resistance. 40 parts by mass or more is more preferable, and 80 parts by mass or more is even more preferable. Blending 200 parts by mass or less of the inorganic filler [D] can further improve mechanical properties and fluidity. 150 parts by mass or less is more preferable, and 100 parts by mass or less is even more preferable.

[0065] The inorganic filler [D] used in the present invention can be used in combination of two or more types. The number and parts by mass of the components used in combination are not particularly limited as long as they are within the range of parts by mass described above.

[0066] When an inorganic filler [D] is further blended, it is preferable that the composition contains 70 to 110 parts by mass of the amorphous resin [B], 0.1 to 40 parts by mass of the component [C], and 0.1 to 200 parts by mass of the inorganic filler [D] per 100 parts by mass of the crystalline polyester resin [A]. This range provides a good balance of heat resistance, low warpage, and mechanical properties, which is preferable.

[0067] [Other ingredients] The resin composition of the present invention may contain one or more optional additives, such as thermoplastic resins other than the components [A] and [B], thermosetting resins such as epoxy resins, antioxidants, heat stabilizers, ultraviolet absorbers, infrared absorbers, light stabilizers, fluorescent brighteners, plasticizers, mold release agents, antistatic agents, anti-drip agents, flame retardants, color inhibitors, and pigments and dyes of various colors such as carbon black, within the scope of the object of the present invention.

[0068] The resin composition of the present invention can be obtained, for example, by melt-kneading the components [A], [B] and [C], and, if necessary, the component [D] and other components.

[0069] Examples of the melt-kneading method include a method in which the components [A], [B], and [C], and if necessary the component [D] and other components, are premixed, and the premixed components are fed to an extruder or the like and melt-kneaded; or a method in which a predetermined amount of each component is fed to an extruder or the like using a metering feeder such as a weight feeder, and the premixed components are melt-kneaded.

[0070] Examples of the premixing include a dry blending method and a mixing method using a mechanical mixer such as a tumbler, a ribbon mixer, a Henschel mixer, etc. The fibrous reinforcing material may also be added by a side feeder installed midway between the base feeder and the vent of a multi-screw extruder such as a twin-screw extruder.

[0071] The composition is preferably granulated before molding. As a granulation method, the polyester resin and other additives are extruded into strands using, for example, a single-screw extruder, twin-screw extruder, triple-screw extruder, conical extruder, or kneader-type mixer equipped with a "Unimelt" or "Dulmage" type screw, and then cut, or extruded in water and cut to form pellets having a length of about 1.5 to 5.0 mm and a diameter of about 1.5 to 5.0 mm, but the granulation method is not limited to these.

[0072] From the viewpoint of productivity, the resin composition of the present invention is preferably kneaded using a twin-screw extruder in order to uniformly mix the components [A], [B], and [C]. The twin-screw extruder is preferably provided with one or more kneading sections, more preferably two or more, in order to improve the dispersibility of each component. For example, when the component [D] is added from a side feeder, the kneading sections are preferably provided at two or more locations: one or more upstream of the side feeder to promote the plasticization and dispersion of the components [A], [B], and [C], and one or more downstream of the side feeder to disperse the component [D] in the resin composition while suppressing breakage.

[0073] The resin composition of the present invention can be melt-molded to obtain films, fibers, and other molded articles in various shapes. Examples of melt-molding methods include injection molding, extrusion molding, and blow molding, with injection molding being particularly preferred.

[0074] In addition to the usual injection molding method, other known injection molding methods include gas-assisted molding, two-color molding, sandwich molding, in-mold molding, insert molding, and injection press molding, and any of these molding methods can be applied.

[0075] Molded articles made from the resin composition according to the present invention can be used for various purposes such as machine mechanism parts, electrical parts, electronic parts and automotive parts, taking advantage of the excellent heat resistance, low warpage and mechanical properties. Specific examples of mechanical parts, electrical parts, electronic parts, and automotive parts include breakers, electromagnetic switches, focus cases, flyback transformers, molded parts for fixing units in copiers and printers, housings for general household electrical appliances and office equipment, variable capacitor case parts, various terminal boards, transformers, printed wiring boards, housings, terminal blocks, coil bobbins, connectors, relays, disk drive chassis, transformers, switch parts, outlet parts, motor parts, sockets, plugs, capacitors, various cases, resistors, electrical and electronic parts that incorporate metal terminals and conductors, computer-related parts, audio parts such as audio components, lighting parts, telegraph equipment-related parts, telephone equipment-related parts, air conditioner parts, home appliance parts such as VTRs and televisions, copier parts, facsimile parts, optical equipment parts, automotive ignition system parts, automotive connectors, housings for head-up displays (HUDs) and engine control units (ECUs), and various automotive electrical parts. [Example]

[0076] Next, the resin composition of the present invention will be specifically described with reference to examples.

[0077] [[B] Production example of acrylonitrile-styrene copolymer] AS Acrylonitrile and styrene were suspension polymerized to prepare beads of AS (acrylonitrile-styrene copolymer, acrylonitrile / styrene = 28 / 72 (weight ratio), MFR = 24.5 g / 10 min). The acrylonitrile / styrene weight ratio was determined by preparing a 1 wt% solution of AS in deuterated dimethyl sulfoxide. 1 H-NMR measurement was carried out and the calculation was carried out based on the following formula: Acrylonitrile weight ratio=(proton integral ratio of proton peaks derived from β methylene of acrylonitrile units between 1.6 and 2.3 ppm) / 2×(molecular weight of acrylonitrile) / ((proton integral ratio of proton peaks derived from β methylene of acrylonitrile units between 1.6 and 2.3 ppm) / 2×(molecular weight of acrylonitrile)+(proton integral ratio of proton peaks derived from aromatic skeleton of styrene units between 6.0 and 7.5 ppm) / 5×(molecular weight of styrene))×100(wt%) Styrene weight ratio=(proton integral ratio of proton peaks derived from the aromatic skeleton of styrene units between 6.0 and 7.5 ppm) / 5×(molecular weight of styrene) / ((proton integral ratio of proton peaks derived from the β-methylene of acrylonitrile units between 1.6 and 2.3 ppm) / 2×(molecular weight of acrylonitrile)+(proton integral ratio of proton peaks derived from the aromatic skeleton of styrene units between 6.0 and 7.5 ppm) / 5×(molecular weight of styrene))×100(% by weight) MFR was determined in accordance with ISO1133-1 (2011) by measuring at 220°C and a load of 10 kg. Epoxy modified AS Acrylonitrile, styrene, and glycidyl methacrylate were suspension polymerized to prepare bead-shaped epoxy-modified AS (acrylonitrile-styrene-glycidyl methacrylate copolymer, acrylonitrile / styrene / glycidyl methacrylate = 25 / 74.7 / 0.3 (weight ratio), MFR = 5.5 g / 10 min). The acrylonitrile / styrene / glycidyl methacrylate weight ratio was determined by preparing a 1 wt% solution of epoxy-modified AS in deuterated dimethyl sulfoxide. 1 H-NMR measurement was carried out and the calculation was carried out based on the following formula: Acrylonitrile weight ratio=(proton integral ratio of proton peaks derived from β methylene of acrylonitrile units between 1.6 and 2.3 ppm) / 2×(molecular weight of acrylonitrile) / ((proton integral ratio of proton peaks derived from β methylene of acrylonitrile units between 1.6 and 2.3 ppm) / 2×(molecular weight of acrylonitrile)+(proton integral ratio of proton peaks derived from aromatic skeleton of styrene units between 6.0 and 7.5 ppm) / 5×(molecular weight of styrene)+(proton integral ratio of proton peaks derived from methyl group of glycidyl methacrylate units between 0.8 and 1.2 ppm) / 3×(molecular weight of glycidyl methacrylate))×100(wt%) Styrene weight ratio=(proton integral ratio of proton peaks derived from the aromatic skeleton of styrene units between 6.0 and 7.5 ppm) / 5×(molecular weight of styrene) / ((proton integral ratio of proton peaks derived from the β-methylene of acrylonitrile units between 1.6 and 2.3 ppm) / 2×(molecular weight of acrylonitrile)+(proton integral ratio of proton peaks derived from the aromatic skeleton of styrene units between 6.0 and 7.5 ppm) / 5×(molecular weight of styrene)+(proton integral ratio of proton peaks derived from the methyl group of glycidyl methacrylate units between 0.8 and 1.2 ppm) / 3×(molecular weight of glycidyl methacrylate))×100(wt%) Glycidyl methacrylate weight ratio = (proton integral ratio of proton peaks derived from methyl groups of glycidyl methacrylate units between 0.8 and 1.2 ppm) / 3 × (molecular weight of glycidyl methacrylate) / ((proton integral ratio of proton peaks derived from β-methylene of acrylonitrile units between 1.6 and 2.3 ppm) / 2 × (molecular weight of acrylonitrile) + (proton integral ratio of proton peaks derived from aromatic skeletons of styrene units between 6.0 and 7.5 ppm) / 5 × (molecular weight of styrene) + (proton integral ratio of proton peaks derived from methyl groups of glycidyl methacrylate units between 0.8 and 1.2 ppm) / 3 × (molecular weight of glycidyl methacrylate)) × 100 (% by weight) MFR was determined in accordance with ISO1133-1 (2011) by measuring at 220°C and a load of 10 kg.

[0078] [Method of measuring each characteristic] In each of the examples and comparative examples, the properties were evaluated by the measurement methods described below.

[0079] 1. Aromatic skeleton content of component [C] (or non-hydrogenated petroleum resin) [C] Prepare a 1% by weight solution of component (or non-hydrogenated petroleum resin) in 1,1,2,2-tetrachloroethane. 1 H-MNR measurement was carried out, and the aromatic skeleton content was calculated from the unit structure of the [C] component (or non-hydrogenated petroleum resin) obtained by the measurement, based on the following formula: Aromatic skeleton content = (proton integral ratio of peaks attributable to protons of the aromatic skeleton from 6.5 to 8.5 ppm) / {(proton integral ratio of peaks attributable to protons other than those of the aromatic skeleton from 0.5 to 5.8 ppm) + (proton integral ratio of peaks attributable to protons of the aromatic skeleton from 6.5 to 8.5 ppm)} × 100 (mol%)

[0080] 2. Hydroxyl value of component [C] According to the neutralization titration method (JIS K0070), 1 g of component [C] was dissolved in 5 mL of 250 g / L acetic anhydride / pyridine solution and heated at 100°C for 1 hour. Then, 1 mL of water was added and the mixture was heated again at 100°C for 10 minutes and cooled to room temperature. An appropriate amount of phenolphthalein / ethanol solution was added to the resulting test solution, followed by titration with a 0.5 N potassium hydroxide ethanol solution. Furthermore, 5 mL of 250 g / L acetic anhydride / pyridine solution without component [C] was heated at 100°C for 1 hour, followed by addition of 1 mL of water, and the mixture was heated again at 100°C for 10 minutes and cooled to room temperature. An appropriate amount of phenolphthalein / ethanol solution was added to the resulting test solution, followed by titration with a 0.5 N potassium hydroxide ethanol solution. The hydroxyl value (unit: mg-KOH / g) was calculated from the titration results obtained above using the following formula: OH=((V0-V)×28.05) / W+AV OH: hydroxyl value of [C] component [mg-KOH / g], V0: titration volume of test solution not containing [C] component [mL], V: titration volume of test solution containing [C] component [mL], AV: acid value of [C] component [mg-KOH / g], W: weight of [C] component [g]

[0081] 3. Heat resistance of resin composition Using a Nissei Plastic Industrial Co., Ltd. NEX1000 injection molding machine, specimens measuring 80 mm in length, 10 mm in width, and 4 mm in thickness were obtained under molding cycle conditions of a molding temperature of 260°C, a mold temperature of 80°C, an injection speed of 50 mm / s, a combined injection time and dwell time of 10 seconds, and a cooling time of 10 seconds. The deflection temperature under load of the resulting specimens was measured at a load of 1.8 MPa in accordance with ISO 75 (2013), and the value was the average of three measurements. Materials with higher deflection temperatures under load were considered to have better heat resistance.

[0082] 4. Low warpage of resin composition Using a Nissei Plastic Industrial Co., Ltd. NEX1000 injection molding machine, a rectangular plate with a diameter of 80 mm and a thickness of 1.0 mm was obtained under molding cycle conditions of a molding temperature of 280°C, a mold temperature of 80°C, an injection speed of 50 mm / s, a combined injection time and dwell time of 10 seconds, and a cooling time of 10 seconds. The resulting rectangular plate was used to measure the diagonal lift height when each of the four corners was parallel to the work table, and the maximum value among the four corners was evaluated as the amount of warpage of the rectangular plate. Materials with smaller amounts of warpage were judged to have better low-warpage properties.

[0083] 5. Mechanical properties of resin compositions Using a Nissei Plastic Industrial Co., Ltd. NEX1000 injection molding machine, notched test specimens measuring 80 mm in length, 10 mm in width, and 4 mm in thickness were obtained under molding cycle conditions of a molding temperature of 260°C, a mold temperature of 80°C, an injection speed of 50 mm / s, a combined injection time and dwell time of 10 seconds, and a cooling time of 10 seconds. The notched Charpy impact strength of the resulting test specimens was measured according to ISO 179 (2010). Materials with higher notched Charpy impact strength were considered to have better mechanical properties.

[0084] 6. Presence or absence of mold contamination Using an injection molding machine (NEX1000 manufactured by Nissei Plastic Industrial Co., Ltd.), rectangular plates measuring 80 mm wide x 80 mm long x 2 mm thick were molded under molding cycle conditions of a molding temperature of 280°C, a mold temperature of 80°C, an injection speed of 50 mm / s, a total injection time and dwell time of 10 seconds, and a cooling time of 10 seconds. After continuously molding 100 rectangular plates, the mold was visually inspected, and evaluation was performed with a score of 0 if there was no adhesion to the vent and a score of △ if there was adhesion to the vent (Table 2).

[0085] <Materials used in Examples and Comparative Examples> (1) [A] Crystalline polyester resin PBT (Polybutylene terephthalate, melting point 225°C, manufactured by Toray Industries, Inc., acid value 22 eq / t, intrinsic viscosity 0.85 dL / g) (2) [B] Amorphous resin AS (acrylonitrile-styrene copolymer, acrylonitrile / styrene = 28 / 72 (weight ratio), MFR = 24.5g / 10min) Epoxy-modified AS (acrylonitrile-styrene-glycidyl methacrylate copolymer, acrylonitrile / styrene / glycidyl methacrylate = 25 / 74.7 / 0.3 (weight ratio), MFR = 5.5g / 10min) (3) [C] component Hydrogenated petroleum resin Plafit E610H (Arakawa Chemical Co., Ltd., aromatic skeleton content 9 mol%, hydroxyl value 50 mg-KOH / g) Imave P-125 (Idemitsu Kosan Co., Ltd., aromatic skeleton content 1 mol%, hydroxyl value 17 mg-KOH / g) Imave S-100 (Idemitsu Kosan Co., Ltd., aromatic skeleton content 9 mol%, hydroxyl value 20 mg-KOH / g) T-REZ HA125 (manufactured by ENEOS Corporation, aromatic skeleton content 1 mol%, hydroxyl value 6 mg-KOH / g) terpene resin YS Resin PX1250 (Yasuhara Chemical Co., Ltd., aromatic skeleton content 1 mol%, hydroxyl value 52 mg-KOH / g) Hydrogenated terpene phenolic resin YS Polyster UH115 (Yasuhara Chemical Co., Ltd., aromatic skeleton content 11 mol%, hydroxyl value 187 mg-KOH / g) Hydroxyl-containing acrylic resin ARUFON UH-2170 (manufactured by Toagosei Co., Ltd., aromatic skeleton content 18 mol%, hydroxyl value 88 mg-KOH / g) (4) [D] Inorganic filler T-187 (glass fiber, manufactured by Nippon Electric Glass Co., Ltd., average fiber diameter 13 μm, average fiber length 3 mm) (5) Other ingredients "Petcol" (registered trademark) 120 (non-hydrogenated petroleum resin, manufactured by Tosoh Corporation, aromatic skeleton content 51 mol%, manufactured by Tosoh Corporation).

[0086] [Examples 1-15, Comparative Examples 1-6] Resin compositions were prepared according to the following procedure, and various physical properties were evaluated using these compositions.

[0087] Using a co-rotating, vented twin-screw extruder (TEX-30α, manufactured by Japan Steel Works, Ltd.) with a screw diameter of 30 mm and an L / D ratio of 35, the [A] crystalline polyester resin, [B] amorphous resin, [C] component, and the other components excluding [D] inorganic filler were mixed according to the composition shown in Table 1 and added to the twin-screw extruder's base section. The [D] inorganic filler was added using a side feeder installed midway between the base section and the vent section. Melt-kneading was performed under extrusion conditions of a kneading temperature of 250°C and a screw rotation of 200 rpm. The resin composition was discharged at a rate of 30 kg / h in the form of strands, passed through a cooling bath, and granulated using a strand cutter. In Comparative Example 6, in which the blending amount of [C] component exceeded 40 parts by mass, the amount of decomposition gas was so large that it was difficult to discharge the resin composition in the form of strands, and the subsequent steps could not be carried out.

[0088] The obtained pellets were dried in a hot air dryer at 110° C. for 6 hours and then evaluated by the above-mentioned method. The results are shown in Table 1.

[0089] Example 1-15, which is a resin composition containing 100 parts by mass of crystalline polyester resin [A], 1 to 110 parts by mass of amorphous resin [B], and 0.1 to 40 parts by mass of component [C], was excellent in heat resistance, low warpage, and mechanical properties.

[0090] Furthermore, when Examples 1-6 and 9 are compared, when the hydroxyl value of the compounded component [C] is 10 mg-KOH / g or more, the deflection temperature under load is 170°C or more, and the notched Charpy impact strength is 12.5 kJ / m 2 The above results indicated that the heat resistance and mechanical properties were superior.

[0091] Comparing Examples 1, 7, 8, and 10-15, when the blending amount of component [C] was 15 parts by mass or more per 100 parts by mass of crystalline polyester resin [A], the notched Charpy impact strength was 12.5 kJ / m 2 These results indicate that the mechanical properties were superior.

[0092] Comparing Examples 7 and 8, Example 7, in which the blending amount of the amorphous resin [B] was increased, had a warpage of 3.0 mm or less, which was superior in low warpage properties, while Example 8, in which the blending amount of the amorphous resin [B] was reduced, had a deflection temperature under load of 170°C or more, which was superior in heat resistance.

[0093] Comparing Examples 1 and 10-12, the greater the blending amount of the amorphous resin [B], the smaller the amount of warpage, and the more excellent the low warpage. The smaller the blending amount of the amorphous resin [B], the higher the deflection temperature under load and the more excellent the heat resistance.

[0094] Comparing Examples 1 and 13-15, the greater the blending amount of component [C], the higher the deflection temperature under load, the lower the amount of warpage, the higher the notched Charpy impact strength, and the better the heat resistance, low warpage, and mechanical properties.

[0095] Comparing Examples 3 and 9, Example 9, which used a hydroxyl group-containing acrylic resin as component [C], was superior in inhibiting mold fouling.

[0096] On the other hand, in both Comparative Examples 1 and 2, which do not contain the [C] component, the notched Charpy impact strength was 10.0 kJ / m 2 In Comparative Example 2, the amount of warpage exceeded 4.0 mm, and the low warpage property was also poor.

[0097] In addition, in Comparative Example 3, in which non-hydrogenated petroleum resin was blended instead of component [C], the deflection temperature under load was less than 160°C and the notched Charpy impact strength was 10.0 kJ / m 2 The heat resistance and mechanical properties were inferior to those of Examples 1-6.

[0098] In Comparative Example 4, in which the blending amount of the amorphous resin [B] exceeded 110 parts by mass per 100 parts by mass of the crystalline polyester resin [A], the deflection temperature under load was less than 160° C., and the heat resistance was poor.

[0099] In Comparative Example 5, which did not contain the amorphous resin [B], the warpage exceeded 4.0 mm, and the low warpage properties were poor.

[0100] [Table 1]

[0101] [Table 2]

Claims

1. A resin composition comprising components [A], [B] and [C], the resin composition comprising 1 to 110 parts by mass of component [B] and 0.1 to 40 parts by mass of component [C] relative to 100 parts by mass of component [A]. [A] Crystalline polyester resin [B] Amorphous resin [C] At least one resin selected from hydrogenated petroleum resins, terpene resins, hydrogenated terpene phenol resins, and hydroxyl group-containing acrylic resins.

2. The resin composition according to claim 1, wherein the component [C] is a resin having a hydroxyl value of 10 mg-KOH / g or more.

3. The resin composition according to claim 1, further comprising component [D] an inorganic filler.

4. The resin composition according to claim 3, comprising 70 to 110 parts by mass of the component [B], 0.1 to 40 parts by mass of the component [C], and 0.1 to 200 parts by mass of the component [D] relative to 100 parts by mass of the component [A].

5. The resin composition according to claim 1, wherein the component [A] is polybutylene terephthalate.

6. The resin composition according to claim 1 , wherein the component [B] is a polymer containing a styrene skeleton.

7. The resin composition according to claim 1, wherein the component [B] is a polymer containing an acrylonitrile skeleton and a styrene skeleton.

8. A molded article made of the resin composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Thermoplastic resin composition

    JP2002179890A

  • Thermoplastic resin composition and molded article

    JP2020186293A